2011
DOI: 10.1108/01409171111178774
|View full text |Cite
|
Sign up to set email alerts
|

Building sustainability in logistics operations: a research agenda

Abstract: Purpose -The purpose of this study is to examine the current state of sustainability efforts within the field of supply chain management, more specifically supply chain logistics operations, and to identify opportunities and provide recommendations for firms to follow sustainable operations. This study also aims to stimulate further research within the area of sustainable logistics operations. Design/methodology/approach -The reasons why it is important to implement sustainability into supply chain operations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
153
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(165 citation statements)
references
References 45 publications
(48 reference statements)
4
153
0
8
Order By: Relevance
“…Em relação especificadamente à logística, ressalta-se que esta se refere ao processo de planejamento, implantação, controle e coordenação dos fluxos de materiais, bens e informações para o lugar apropriado, no momento desejado e em quantidades ótimas, de modo a maximizar a rentabilidade atual e futura (Bruzzone, Tremori, Massei, & Tarone, 2009;Beškovnik & Jakomin, 2010;Dey, LaGuardia, & Srinivasan, 2011;Tamulis, Guzavičius, & Žalgirytė, 2012). Portanto, a logística não se restringe apenas às atividades de transporte, apesar de este ser um de seus elementos de destaque, principalmente em função do custo envolvido.…”
Section: Green Logisticunclassified
See 2 more Smart Citations
“…Em relação especificadamente à logística, ressalta-se que esta se refere ao processo de planejamento, implantação, controle e coordenação dos fluxos de materiais, bens e informações para o lugar apropriado, no momento desejado e em quantidades ótimas, de modo a maximizar a rentabilidade atual e futura (Bruzzone, Tremori, Massei, & Tarone, 2009;Beškovnik & Jakomin, 2010;Dey, LaGuardia, & Srinivasan, 2011;Tamulis, Guzavičius, & Žalgirytė, 2012). Portanto, a logística não se restringe apenas às atividades de transporte, apesar de este ser um de seus elementos de destaque, principalmente em função do custo envolvido.…”
Section: Green Logisticunclassified
“…Sua preocupação está voltada para as variáveis custo, tempo e economia, e não abrangem questões ambientais (Wu & Dunn, 1995;Seroka-Stolka, 2014). Contudo, a preocupação e sensibilização com os efeitos das ações desordenadas como a poluição, o congestionamento, o esgotamento de recursos, a eliminação de resíduos perigosos, a geração de ruídos e a degradação ambiental tem feito com que a visão dos processos logísticos seja estendida também às questões de cunho social e ambiental (Rodrigue et al, 2001;Bruzzone et al, 2009;Beškovnik & Jakomin, 2010;Dey et al, 2011;Zhao, 2014).…”
Section: Green Logisticunclassified
See 1 more Smart Citation
“…FedEx reported that the hybrid trucks reduced carbon emissions by 30% in the U.S. [29]. For reference, low carbon technologies for logistics operations are presented in Dey et al [30] and McKinnon [22].…”
Section: Modeling Of the Direct Shipment Strategymentioning
confidence: 99%
“…Issues related to social sustainability (Presley et al, 2007;Sarkis et al, 2010) as well as environmental sustainability (Lieb and Lieb, 2010;Dey et al, 2011) are discussed. All these works are confined to the above mentioned topics in logistics and no article is found in transportation service procurement.…”
Section: Introductionmentioning
confidence: 99%